A gender and social inclusion lens on resilience in the context of climate change, COVID and other shocks and stresses - Kosec, Katrina; Clayton, Amanda; Dulani, Boniface; Robinson, Amanda (International Food Policy Research Institute, 2023)
Interventions to combat climate change often strive to promote gender balance so that men and women have an equal right to participate in and benefit from these programs. Yet whether and how women’s participation affects climate governance is still poorly understood. We examine the causal effect of women’s representation in climate-related deliberations using the case of communally managed forests in rural Malawi. We run a lab-in-the-field experiment that randomly varies the gender composition of six-member groups asked to deliberate and then vote on solutions to combat deforestation. We find that women have relatively more influence in group decisions when they make up a larger share of the group. Our initial results suggest that this is due to women being increasing recognized for their contributions, rather than substantial changes in participants’ speech patterns in groups with more women. When women are in the majority, they are more likely to sway group decisions to meet their pre-treatment preferences. These findings suggest that including women in decision-making can shift deliberative processes and outcomes in support of historically marginalized resource users.